Saras Cranes in Palwal District in Southern Haryana are Asking for Immediate Attention for Their Last Rescue Effort - Tirshem Kumar Kaushik; Rohtash Chand Gupta; Parveen Kumar Vats (Journal of Tropical Life Science, 2015)
Saras Cranes Grus antigone are endangered birds of open wetlands with highly worrying depletion trends being witnessed related with disappearance of marshy and shallow perennial, expansive wetlands throughout northern India. Alongside, massive hunting in 18th, 19th and 20th centuries and even today is another serious cause for their worrisome deterioration. Also, destruction of nests, eggs, fledglings and adults by aboriginals indeliberately or deliberately is causing these cranes to perish sooner than latter, completely. Now, Saras Cranes are found in limited number and domain as four populations in the entire world including India, China, Burma, South East Asia and northern Australia. The population of Indian Saras Crane is pitiably restricted to Etawa and Mainpuri districts of Uttar Pradesh. Stray birds of this species are restricted to Kanha National Park in Madhya Pradesh and in some parts of Gujarat and Assam. It is interesting to note that few pairs have been seen in Faridabad and Palwal districts in southern Haryana, India. These need to be protected and conserved.